Integrative Multiparametric Analysis of Circulating Cell‐Free Nucleic Acids of Plasma in Healthy Individuals During Aging - Tessier, Nicolas P.; Hardy, Lise M.; Mauger, Florence; Daunay, Antoine; Daviaud, Christian; Hchaichi, Ilef; Horgues, Caroline; Sahbatou, Mourad; Le Buanec, Hélène; Deleuze, Jean‐François; How‐Kit, Alexandre (Aging cell, 2025)
Plasma circulating cell‐free nucleic acids (ccfNAs) provide an exceptional source of information about an individual's health, yet their biology in healthy individuals during aging remains poorly understood. Here, we present the first integrative multiparametric analysis of the major types of plasma ccfNAs, including nuclear (ccfnDNA) and mitochondrial (ccfmtDNA) DNA, as well as ribosomal (ccfrRNA), messenger (ccfmRNA) and micro‐RNA (ccfmiRNA) in 139 healthy donors aged 19–66 years. We focused on quantity, integrity, and DNA methylation using an optimized experimental workflow that combines highly sensitive analytical methods with the detection of highly repetitive DNA and highly abundant RNA sequences, thereby reducing the required amount of ccfNAs per analysis. We showed a highly significant increase in ccfnDNA levels during aging ( p < 0.001), associated with a decrease in its integrity ( p < 0.05), while no significant changes were detected in ccfmtDNA levels and ccfDNA methylation. Moreover, a significant increase in ccfmRNA and ccfrRNA ( p < 0.05), as well as miR‐483‐5p ( p < 0.001) levels was detected during aging, but without any changes in ccfRNA integrity. Finally, we also showed that ccfDNA and ccfRNA levels were correlated ( p < 0.001), and a similar pattern was observed for ccfmtDNA and ccfRNA levels, suggesting a possible common release, maintenance, and/or clearance mechanism. Therefore, our study provides an optimized workflow for the global analysis of ccfNAs, enhances the understanding of their biology during aging, and identifies several potential ccfNA‐based biomarkers of aging.